Clinical Patterns and Mycological Profile of Onychomycosis in a Tertiary Care Hospital in Dhaka (Bangladesh Medical Journal, 2026)
Onychomycosis is a common chronic fungal infection of the nails that significantly affects both physical health and quality of life. Accurate identification of clinical patterns and the fungi responsible is vital for effective treatment and prevention of recurrence. Its clinical presentation and etiological agents vary across geographical regions, necessitating region-specific data to guide diagnosis and management. This cross-sectional study was conducted in the Department of Dermatology and Venereology of a tertiary care hospital in Dhaka. A total of 139 clinically suspected cases of onychomycosis were included. A detailed clinical evaluation was performed to classify the types of onychomycosis. Nail specimens were collected and subjected to direct microscopy using a potassium hydroxide (KOH) mount and fungal culture for confirmation and identification of causative organisms. Data were analyzed using appropriate descriptive statistics and presented as frequencies and percentages. Among the 139 patients, the most common clinical type was distal lateral subungual onychomycosis (DLSO), observed in more than half (51.08%) of cases. Toenail involvement was more frequent (60.43%) than fingernail. The highest proportion of patients (33.81%) belonged to the 21–30 years age group, with a mean age of 45.02 ± 10.89 years, and a female predominance (61.15%). Direct microscopy by KOH mount was positive in nearly half (46.76%) of cases. Fungal culture demonstrated that dermatophytes were the predominant isolates (50.36%), followed by Candida spp. (7.91%). The remaining cases were either non-dermatophyte molds or culture-negative. These findings indicate a predominance of dermatophyte infections in this population, although non-dermatophyte organisms also contribute to the disease burden. Onychomycosis in this tertiary care setting is predominantly characterized by DLSO, toenail involvement, and a higher prevalence among young adults and females, with dermatophytes as the principal etiological agents. The moderate positivity rate of KOH microscopy highlights its utility as a screening tool, while fungal culture remains essential for definitive diagnosis. These findings underscore the importance of combined clinical and mycological evaluation for accurate diagnosis and effective management of onychomycosis.Bangladesh Med J. 2025 May; 54(2): 7-12